Site symmetry approach applied to the supercell model of MgAl2O4 spinel with oxygen interstitials: Ab initio calculations - Evarestov, Robert A.; Platonenko, Alexander; Zhukovskii, Yuri F. (Elsevier B.V., 2018)
In this study we simulate structural, electronic and phonon properties of MgAl2O4 spinel containing a single neutral oxygen interstitial (Oi) per crystalline L4 and L8 supercells, e.g., its dumbbell formed with one of the nearest regular oxygen atoms of the lattice (Oi-Oreg). Due to the splitting of the Wyckoff positions in supercell models of a perfect crystal, five possible Oi positions with different site symmetry have been identified and studied (C1, Cs, C3v D2d and Td). First principles hybrid HSE06 DFT functional calculations on perfect and defective spinel structures have been accompanied by geometry optimization. The calculated properties of spinel crystal (lattice constants, bulk modulus, band gap as well as frequencies of infrared- and Raman-active vibrational modes) are in a good qualitative agreement with the corresponding experimental data. The formation energy of Oi is found to be minimal for the interstitial site of the lowest symmetry (C1). The results obtained are important, in particular, for understanding the radiation and chemical stability as well as other key properties of MgAl2O4 spinel-type oxide crystals.
This study has been carried out within the framework of the EUROfusion Consortium and has been provided funding from the Euratom research and training programme 2014-2018 under grant agreement No 633053. The authors are indebted to E.A. Kotomin, A.I. Popov and R. Vila for stimulating discussions. The views and opinions expressed herein do not necessarily reflect those of the European Commission. Calculations have been performed using both the Marconi supercomputer system at the Computational Simulation Centre (Italy) and the Computer Center of St. Petersburg State University.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; MgAl2O4 spinel; Single neutral oxygen interstitial; Site symmetry; First principles calculations